2207: A Phase I dose escalation trial of nab-paclitaxel and fixed dose radiation in patients with unresectable or borderline resectable pancreatic cancer - Ezra Shabason, Jacob (J Clin Transl Sci, 2018)
OBJECTIVES/SPECIFIC AIMS: Patients with locally advanced pancreatic cancer typically have poor outcomes, with a median survival of ~16 months. Novel methods to improve local control are needed. Nab-paclitaxel (abraxane) has shown efficacy in pancreatic cancer and is FDA approved for metastatic disease in combination with gemcitabine. Nab-paclitaxel is also a promising radiosensitizer based on laboratory studies, but it has never been clinically tested with definitive radiotherapy for locally advanced disease. METHODS/STUDY POPULATION: We performed a phase 1 study using a 3+3 dose-escalation strategy to determine the safety and tolerability of dose escalated nab-paclitaxel with fractionated radiotherapy for patients with unresectable or borderline resectable pancreatic cancer. Following induction chemotherapy with 2 cycles of nab-paclitaxel and gemcitabine, patients were treated with weekly nab-paclitaxel and daily radiotherapy to a dose of 52.5 Gy in 25 fractions. Final dose-limiting toxicity (DLT) determination was performed at day 65 after the start of radiotherapy. RESULTS/ANTICIPATED RESULTS: Nine patients received nab-paclitaxel at a dose level of either 100 mg/m(2) (n=3) or 125 mg/m(2) (n=6). One DLT (grade 3 neuropathy) was observed in a patient who received 125 mg/m(2) of nab-paclitaxel. Other grade 3 toxicities included fatigue (11%), anemia (11%), and neutropenia (11%). No grade 4 toxicities were observed. With a median follow-up of 8 months (range 5–28 months), median survival was 19 months and median progression-free survival was 10 months. Following chemoradiation, 3 patients underwent surgical resection, all with negative margins and limited tumor viability. Of the 3 patients, 2 initially had borderline resectable tumors and 1 had an unresectable tumor. Tumor (SMAD-4, Caveolin-1) and peripheral (circulating tumor cells and microvesicles) biomarkers were collected and are being analyzed. DISCUSSION/SIGNIFICANCE OF IMPACT: The combination of fractionated radiation and weekly nab-paclitaxel was safe and well tolerated. This regimen represents a potentially promising therapy for patients with unresectable and borderline resectable pancreatic cancer and warrants further investigation.